The effects of standardized ileal digestible tryptophan:lysine ratio in nursery and finishing pigs; and regression analysis to predict growth performance from dietary net energy - Nitikanchana, Sureemas (Kansas State University, 2013)
A total of 8 experiments and a meta-analysis were performed with the overarching goal to improve amino acid and energy utilization in swine diets. The first experiment used a total of 255 nursery pigs to evaluate the optimum dietary standardized ileal digestible (SID) tryptophan to lysine (Trp:Lys) ratio. Four experiments also were conducted using 6,668 finishing pigs to determine the effects of SID Trp:Lys ratio in diets containing dried distillers grains with solubles (DDGS) on growth performance and carcass characteristics. A subsequent experiment evaluated the interaction between Trp and large neutral amino acids (Trp:LNAA) on growth performance of early and late-finishing pigs. Lastly, data from 41 trials and 2 validation trials were used to develop a regression equations to predict ADG or gain to feed (G:F) as influenced by BW and net energy (NE) content in growing-finishing pigs. In Exp. 1, the growth performance and economics indicated the optimum SID Trp concentration for 6-to 10-kg nursery pigs at 20.3% of Lys. In Exp. 2, 3, and 4, there were no differences in growth performance due to SID Trp:Lys ratio; however, increasing the SID Trp:Lys ratio suggested an opportunity to improve carcass yield and lean in pigs fed high levels of DDGS. Experiment 5 indicated an optimum SID Trp:Lys ratio of 20% for 71- to 127-kg pigs fed high level of DDGS. In Exp. 6, growth performance was unaffected by dietary treatment suggesting that 16.5% SID Trp:Lys was adequate to prevent a negative impact on growth when SID Trp:LNAA was as low as 3.0% in finishing period. Overall, the experiments suggested a higher optimum SID Trp:Lys ratio than is currently standard practice. The regression analysis from the meta-analysis showed that increasing dietary NE improved ADG and G:F. However, the magnitude of improvement will be minimized if the SID Lys concentration is limiting. The validation experiments indicated that the prediction equations provided a good estimation of growth rate and feed efficiency of growing-finishing pigs fed different levels of dietary NE except for pigs fed the diet with DDGS. These predictions of growth performance can then be used to model economic value of different dietary energy strategies.
Keywords: Tryptophan; Net energy; Pig; Animal Sciences (0475)